Improving Students’ Vocabulary In Descriptive Text By Using The Bingo Game - Via Oktaviani; Eusabinus Bunau; Wardah Wardah; Yohanes Gatot Sutapa Yuliana; Luwandi Luwandi (Journal on Education, 2024)
This research aimed to improve students’ vocabulary by using the Bingo Game to the seventh grade students of SMP Negeri 04 Teluk Keramat in academic year 2022/2023. The research was conducted in class VII C which consisted of 24 students. The method applied in this research was Classroom Action Research. This research was carried out in two cycles. In this research, the data was collected by using field note, an observation checklist and an individual test. The result of the research showed that the use of the Bingo Game could gradually improve the students’ vocabulary. By using the Bingo Game, the students were able to actively participate in the teaching and learning process, understanding the meaning and description of the target vocabulary. Moreover, the significant improvement can also be seen from the number of students whose scores reached the standard minimum score. In the cycle 1, there were only 9 students whose scores reached the standard minimum score and there were 15 students who could not reach the standard minimum score for English Subject. However, all of the students passed the standard minimum score in cycle 2. Therefore, this research had gradually improved the students’ vocabulary by using the Bingo Game.